2015
DOI: 10.1186/s12955-015-0298-1
|View full text |Cite
|
Sign up to set email alerts
|

An up-date on health-related quality of life in myasthenia gravis -results from population based cohorts

Abstract: Current available therapies control Myasthenia gravis (MG) reasonably well, but Health Related Quality of life (HRQOL) remains lower than expected. The aim was provide insights in how HRQOL in MG stands across borders and time, compare the scores to general population controls and other chronic disorders and assess the impact of potential predictors for quality of life such as a) clinical characteristics b) antibodies c) thymoma and d) treatment in a population-based cohort.MethodsWe designed a population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
74
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 38 publications
11
74
2
Order By: Relevance
“…27,[38][39][40] Our study showed female sex, generalized disease, and lack of employment to be associated with reduced HRQOL, comparable to results in 2 large MG studies. 27,41 In contrast to the pattern of muscle weakness, the mRS score as a marker for disease severity did not independently predict HRQOL. This could be related to the limited number of patients, limited overall variation in mRS scores, or confounding by also including the pattern of weakness in the model.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…27,[38][39][40] Our study showed female sex, generalized disease, and lack of employment to be associated with reduced HRQOL, comparable to results in 2 large MG studies. 27,41 In contrast to the pattern of muscle weakness, the mRS score as a marker for disease severity did not independently predict HRQOL. This could be related to the limited number of patients, limited overall variation in mRS scores, or confounding by also including the pattern of weakness in the model.…”
Section: Discussionsupporting
confidence: 87%
“…Nonresponders were reminded twice. Control cohorts were a population-based cohort of 464 patients with myasthenia gravis (MG) in the Netherlands collected at the same time 27 and published normative data in the Dutch general population. 28 The SF-36 is organized into 8 domains, with a score ranging from 0 (worst HRQOL) to 100 (best HRQOL).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…We also found that men had a significantly higher ACTIVLIM. This finding is in agreement with several large international studies in which a higher health‐related quality of life (HRQoL) was found in men with MG . Furthermore we found that patients with an additional AID had significantly more limitations in ADL.…”
Section: Discussionsupporting
confidence: 93%
“…No statistically significant differences between HRQOL at patients with diagnosed myasthenia versus general population were found. Nevertheless, it was observed that certain conditionings, such as female gender, general fatigability or usage of secondary non-steroid immunosuppressive were risk factors to reduced HRQOL [25].…”
Section: Discussionmentioning
confidence: 99%